PERBEDAAN PERKEMBANGAN MOTORIK BALITA STUNTING DAN NORMAL DI WILAYAH KERJA PUSKESMAS PEGANG BARU - Eka Putri Primasari; Putri Nelly Syofiah; Gina Muthia (Universitas Pahlawan, 2021)
ABSTRACT Stunting is a condition of failure in the growth period (body and brain) of toddlers due to long-term malnutrition. The incidence of stunting can inhibit motor development in children. WHO data for 2019 states, that 21.3% of all toddlers in the world are stunted. The prevalence of stunting for the South-eastern Asia region in 2020 is 24.1 with an estimated number of stunting cases of 13.5 million cases. In Indonesia, it is known that 11.5% of toddlers are very short and 19.3% are short. In West Sumatra, there are 9.6% very short children under five and 20.3% short children. The percentage of stunting cases in Pasaman Regency was 25.1% and stunting cases was quite high in the working area of Puskesmas Pegang Baru, Pasaman Regency ( 16.8%) . This study aims to analyze the differences in motor development between stunting and normal toddlers in the working area of Puskesmas Pegang Baru, Pasaman Regency. This type of research is analytic with the approach used cross sectional study. The number of samples in the study were 130 toddlers. Motor development data were obtained through the KPSP format. The statistical test used was the chi square test. The results showed that there were differences in the development of fine morotic (p-value = 0,000) and gross morotic (p-value = 0.002) between stunting and normal toddlers. Therefore it is very necessary to monitor the growth and development of toddlers on a regular basis according to the age of the toddler, so as to minimize the occurrence of disruption to growth and development in toddlers. ABSTRAK Stunting merupakan kondisi gagal dalam masa pertumbuhan (tubuh dan otak) balita akibat kekurangan gizi dalam waktu yang lama. Kejadian stunting dapat menghambat perkembangan motorik pada anak. Data WHO tahun 2019 menyebutkan 21,3% dari semua balita di dunia mengalami stunting. Prevalensi stunting untuk wilayah South-eastern Asia tahun 2020 adalah 24,1 dengan perkiraan jumlah kasus stunting sebanyak 13,5 juta kasus. Di Indonesia diketahui terdapat 11,5% balita sangat pendek dan 19,3% balita pendek. Di Sumatera Barat terdapat 9,6% balita sangat pendek dan 20,3% balita pendek. Persentase kasus stunting untuk di Kabupaten Pasaman yaitu 25,1% dan Kasus stunting cukup tinggi di wilayah kerja Puskesmas Pegang Baru, Kabupaten Pasaman yaitu 16,8%. Penelitian ini bertujuan menganalisis perbedaan perkembangan motorik antara balita stunting dan balita normal di wilayah kerja Puskesmas Pagang Baru Kabupaten Pasaman. Jenis penelitian bersifat analitik dengan pendekatan yang digunakan adalah cross sectional Jumlah.sampel dalam penelitian sebanyak 130 balita. Data perkembangan motorik diperoleh melalui format KPSP. Uji statistik yang digunakan adalah uji chi square. Hasil penelitian didapatkan adanya perbedaan perkembangan morotik halus (p-value=0,000) dan morotik kasar (p-value=0,002) antara balita stunting dengan balita normal. Oleh karena itu sangat diperlukan pemantauan pertumbuhan dan perkembangan balita secara rutin sesuai dengan usia balita, sehingga dapat meminimalkan terjadinya gangguan terhadap tumbuh kembang pada balita.